Optic Nerve Head Perfusion Before and After Intravitreal Antivascular Growth Factor Injections Using Optical Coherence Tomography-based Microangiography. Issue 3 (March 2019) - Wen, Joanne C.; Chen, Chieh-Li; Rezaei, Kasra A.; Chao, Jennifer R.; Vemulakonda, Atma; Luttrell, Ian; Wang, Ruikang K.; Chen, Philip P.
Abstract : Purpose: To use optical coherence tomography angiography (OCTA) to evaluate the changes in optic nerve head perfusion following intravitreal antivascular endothelial growth factor injections. Methods: Preinjection and postinjection intraocular pressure (IOP) and OCTA images were taken of both the injected and uninjected fellow eyes. Results: Mean preinjection IOP was 16.6±4.7 mm Hg, which increased to a mean of 40.3±13.0 mm Hg ( P <0.0001) during the first postinjection image and remained elevated at 36.1±11.5 mm Hg ( P <0.0001) during the second postinjection image. Although no significant change was observed in flux, vessel area density, or normalized flux when comparing the OCTA preinjection and first postinjection images, a significant decrease at the second postinjection image was observed ( P =0.03, 0.02, and 0.03, respectively). No significant change was observed in the uninjected fellow eye during the same time period ( P =0.47, 0.37, and 0.38, respectively). Conclusions: Following an antivascular endothelial growth factor injection, mean IOP increased significantly and OCTA imaging of the optic nerve demonstrated a mild but significant decrease in optic nerve head perfusion parameters. Clinicians performing these injections should be aware of these findings and monitor the status of the optic nerve in patients undergoing injections.